Analisis Nilai Tambah Agroindustri Cokelat Tahu (Studi Kasus Di Wijaya Kembar Sukses Kota Kediri) - Dwi Septiani, Avita Risky; Maharani, Navita; Nurul Choirina, Vifi; Setiyadi, Heru (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2024)
The purpose of this research is to determine the process of processing tofu chocolate, to know the added value and profits, as well as the Net Profit Margin (NPM) obtained from the tofu chocolate agroindustry. This research was conducted from November to December 2023, which took place at the Wijaya Kembar Sukses located on Jalan Tinalan IV Timur, Number 1, Pesantren District, Kediri City. The method used in this study is a quantitative descriptive method, which describes the condition of the research with data in the form of number. The data analysis methods used are the Hayami and NPM (Net Profit Margin).The results of the study show that the tofu chocolate processing process includes the stages of tool and material preparation, tofu cutting, tofu frying, tofu slicing, chocolate melting, printing, cooling, and packaging. he added value of chocolate tofu using the Hayami method is included in the high criteria. It is necessary to carry out further research on marketing strategies and business development so that people are more familiar with tofu chocolate products and can increase sales volume.